Decade-long soil changes after the clear felling in forests of the North-Western Caucasus mountains - Shkhapatsev, Aslan; Vilkova, Valeria; Soldatov, Vasiliy; Kazeev, Kamil; Kolesnikov, Sergey (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2023)
Clear-fell harvesting significantly alters ecosystem attributes at multiple spatial scales. The results of a study of the dynamics of changes in Rendzik Leptosol and Greyic Phaeozem Vertic forests in the middle mountains of the North-Western Caucasus after clear-cutting in 2010-2020 are presented. Immediately after clearing the forest, areas with varying degrees of disturbance of the soil and vegetation cover were identified in the clearings, from maximum disturbance in the central part of the clearing to slight disturbance on their periphery at different elevations of 540-1600 meters above sea level (masl). The soil covering is represented with Rendzik Leptosol and Greyic Phaeozem Vertic. Among used metrics were temperature, humidity, texture density, penetration resistance, structural and aggregate composition, and other soil parameters. On felling areas, increased temperatures and decreased soil humidity were recorded. The temperature of Rendzik Leptosol at a depth of 10-30 cm changes within the range of 1-15°С in the period 2018-2020. The terrain elevation affects the soil due to the temperature gradient significantly. Rendzik Leptosol is much colder at an elevation 1640 meters above sea level than at 1200 meters above sea level. The temperature of Phaeozem (540 meters above sea level) reaches 20°С during the summer months at a depth of 10 cm. Soils in felling have differences in structural and aggregate composition and water resistance of aggregates. The study results can be used in assessing damage to ecosystems after deforestation and developing methods for accelerating the restoration of soil properties after deforestation. The result of the study can be applied to assess the change in the state of ecosystems after forest degradation. The most informative diagnostic indicators for assessing the state of ecosystems after forest degradation are discussed in the article.